2008
DOI: 10.1182/blood-2008-04-151043
|View full text |Cite|
|
Sign up to set email alerts
|

UV-C irradiation disrupts platelet surface disulfide bonds and activates the platelet integrin αIIbβ3

Abstract: UV-C irradiation has been shown to be effective for pathogen reduction in platelet concentrates, but preliminary work indicated that UV-C irradiation of platelets can induce platelet aggregation. In this study, the mechanism underlying this phenomenon was investigated. Irradiation of platelets with UV-C light (1500 J/m 2 ) caused platelet aggregation, which was dependent on integrin ␣IIb␤3 activation (GPIIb/IIIa). This activation occurred despite treatment with several signal transduction inhibitors known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 22 publications
9
67
0
Order By: Relevance
“…20 Similar to our patients, the leukocyte extravasation was also defective in caldaggef1 knockout mice. 8 We therefore performed complete genomic sequencing of all coding exons from the CALDAGGEF1 gene.…”
Section: Homozygosity Mappingsupporting
confidence: 85%
“…20 Similar to our patients, the leukocyte extravasation was also defective in caldaggef1 knockout mice. 8 We therefore performed complete genomic sequencing of all coding exons from the CALDAGGEF1 gene.…”
Section: Homozygosity Mappingsupporting
confidence: 85%
“…Indeed, disruption of disulfide bonds of αIIbβ3 by UVC may be responsible for the increased aggregability and PAC-1 binding detectable in UVC-treated platelets. However, the conditions in the study by Verhaar et al [40], including plasma content, platelet concentration, intensity and time for UVC delivery, type of irradiation vessel and agitation, were completely different from those used in the THERAFLEX UV-Platelets irradiation procedure (table 3). As already mentioned above, the treatment conditions have significant influence on the biological effects of UVC and, thus, on the quality of the product.…”
Section: In Vitro Qualitymentioning
confidence: 99%
“…In a recent biochemical study by Verhaar et al [40], it was reported that UVC irradiation exerts a direct effect on αIIbβ3 (and other integrins) by modifying extracellular disulfide bonds regulating integrin conformation. This direct activation of platelet αIIbβ3, the fibrinogen receptor, may result in aggregation of stored platelets and influence the hemostatic function of the platelets.…”
Section: In Vitro Qualitymentioning
confidence: 99%
“…Thus, UV activate gene expression of a2, a1 and a5 in skin mice (Kligman et al, 1999), as well as they stimulate the activity of b1 subunit in fibroblasts and of a2b3 dimer in platelets (Verhaar et al, 2008).…”
Section: Impact Of Uv On Integrin Expression and Functionmentioning
confidence: 99%